Computer-based medical education in Benha University, Egypt: knowledge, attitude, limitations, and suggestions. Issue 4 (December 2016) - Bayomy, Hanaa; El Awadi, Mona; El Araby, Eman; Abed, Hala A.
Abstract : Background: Computer-assisted medical education has been developed to enhance learning and enable high-quality medical care. This study aimed to assess computer knowledge and attitude toward the inclusion of computers in medical education among second-year medical students in Benha Faculty of Medicine, Egypt, to identify limitations, and obtain suggestions for successful computer-based learning. Participants and methods: This was a one-group pre–post-test study, which was carried out on second-year students in Benha Faculty of Medicine. A structured self-administered questionnaire was used to compare students' knowledge, attitude, limitations, and suggestions toward computer usage in medical education before and after the computer course to evaluate the change in students' responses. Results: The majority of students were familiar with use of the mouse and keyboard, basic word processing, internet and web searching, and e-mail both before and after the computer course. The proportion of students who were familiar with software programs other than the word processing and trouble-shoot software/hardware was significantly higher after the course ( P <0.001). There was a significant increase in the proportion of students who agreed on owning a computer ( P =0.008), the inclusion of computer skills course in medical education, downloading lecture handouts, and computer-based exams ( P <0.001) after the course. After the course, there was a significant increase in the proportion of students who agreed that the lack of central computers limited the inclusion of computer in medical education ( P <0.001). Although the lack of computer labs, lack of Information Technology staff mentoring, large number of students, unclear course outline, and lack of internet access were more frequently reported before the course ( P <0.001), the majority of students suggested the provision of computer labs, inviting Information Technology staff to support computer teaching, and the availability of free Wi-Fi internet access covering several areas in the university campus; all would support computer-assisted medical education. Conclusion: Medical students in Benha University are computer literate, which allows for computer-based medical education. Staff training, provision of computer labs, and internet access are essential requirements for enhancing computer usage in medical education in the university.